(untitled) (Journal of the College of Basic Education, 2025)
The research aims to identify the effectiveness of the (Do-Review-Study-Apply) strategy in acquiring physics concepts among second-grade intermediate female students. The null hypothesis was imposed, stating: "There is no statistically significant difference at the level of (0.05) between the average scores of the experimental group students who studied physics according to the (Do-Review-Study-Apply) strategy and the average scores of the control group students who studied the same subject according to the traditional method of acquiring physics concepts." The experimental design with partial control was adopted for two equivalent groups (chronological age, intelligence (RAFN), and prior knowledge). To achieve the research objective, a random sample of (76) female students was selected from "Martyr Adel Nasser Secondary School" affiliated with the Karbala Education Directorate. They were divided into two groups: the experimental group (39) students and the control group (37) students, for the first semester of the academic year (2024-2025). The duration of the experiment was nine weeks, and the study material consisted of the first three chapters of the physics book. The second intermediate level included (150) behavioral objectives. (18) study plans were prepared for each group, along with (10) main concepts and (52) sub-concepts. Based on these, a physical concepts acquisition test was prepared, which included (30) items, and its validity and reliability were verified. The following statistical methods were used: (Kuder-Richard-20 equation, the coefficient of ease, difficulty, discrimination, and effectiveness of false alternatives, t-test, chi-square, and Cohen’s equation) to verify the research results. After applying the research tool to the research sample, the results showed that the students in the experimental group outperformed the students in the control group in the (physical concepts acquisition test). Based on this, conclusions, recommendations, and proposals were presented.